Negotiating community engagements and alliances :|Queer People of Color and Turkish migrants in Berlin - Altay, Mehmet Tunay. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis focuses on the relationship between queer people of color communities and new wave Turkish LGBTQ migrants in Berlin to understand how the perception of race/ethnicity plays a role in forming political alliances. In doing so, the thesis is centered on three main questions: "How do QPoC politics and place-making practices influence new wave Turkish LGBTQ migrants’ mobility in Berlin?", "What are the impacts of QPoC on new wave Turkish LGBTQ migrants’ understanding of race and ethnicity?", and finally "What are the impacts of QPoC communities on new wave Turkish LGBTQ migrants’ understanding of solidarity and transnational alliance?". Qualitative research of this thesis involves in-depth interviews with twelve participants between 24 and 33 years old, qualitative content analysis, and participant observation. The findings of this thesis argue that the experience of the participants as a group of racially ambiguous new migrants in Berlin complicates the binary distinction between "white" and "person of color" both in participants spatial interactions with QPoC safe space strategies and in their racial / ethnic self-identification. Moreover, this thesis shows that the study of critical ethnicity and identity have to take into consideration the racial dynamics of migrants' "homeland”. Overall, the ambivalent relationship between the participants and the QPoC challenges to the classic representation of Turkish migrants as being stuck "between-two-worlds" and discusses that the participants have expanded to multiple trans-local activities interconnected with other urban minority groups under QPoC in Berlin.
Keywords: Germany -- Emigration and immigration.; Sexual minority community.